The Invention of Capitalism : Classical Political Economy and the Secret History of Primitive Accumulation - Perelman, Michael (Book collections on Project MUSE., 2000)
Rethinks the history of classical political economy by assessing the Marxian idea of "primitive accumulation," the process by which a propertyless working class is created.